GD-OES Investigations of Lithium-Ion Battery Graphite Anodes: Impact of Plasma Parameters and Electrode Properties - Langer, Frauke; Utami, Anggraini; Kirres, Jochen; Krämer, Elisabeth; Bachmann, Julien (ACS Applied Materials and Interfaces, 2023)
Due to the demand of lithium-ion battery investigations with glow discharge optical emission spectroscopy (GD-OES), a fundamental study of the influence of essential GD-OES parameters toward graphite anodes in an argon plasma was conducted and compared to previous investigations of massive materials. It is shown that increased applied voltage (500-700 V) enhances the sputtering rate by up to 100%/100 V while keeping the crater shape unaffected. In contrast to this, gas pressure variation seems to be the main tool for crater shape adjustment. Enhancement of the gas pressure (160-300 Pa) pushes the crater profile from a concave to flat shape and to concave again. Known plasma effects are discussed and correlated with the observations. A set of measuring parameters providing a good balance between the crater shape and the sputtering rate is proposed. Additionally, an increase of the duty cycle in the pulsed glow discharge mode leads to a linear increase of the sputtering rate, while a pulse duration rise enhances the sputtering rate in a nonlinear fashion. Thus, different pulsing conditions represent instruments for enhancement of the sputtering rate without affecting the crater shape significantly. Our investigation of different electrode densities shows that lower densities lead to a larger sputtered volume as well as a larger concavity of the released crater.
CRIS-Team Scopus Importer:2023-12-08
Keywords: analytics; energy materials; GD-OES; glow discharge; graphite anode; lithium-ion battery; plasma; spectroscopy